Tracking millennial-scale climate variability during the last glacial period using aquatic productivity indicators from Lake Suigetsu, Japan - Vanessa Nowinski; Alexander Francke; John Tibby; Takeshi Nakagawa; Tony Hall; Ikuko Kitaba; Jonathan Tyler (Quaternary Science Reviews, 2025)

Revealing the timing and dispersal of large explosive eruptions at Aso volcano (Japan) by integrating proximal and distal tephra records over the last 130 kyrs - Sophie O. Vineberg; Paul G. Albert; Danielle McLean; Takehiko Suzuki; Yasuo Miyabuchi; Hideo Hoshizumi; Hannah M. Buckland; Gwydion Jones; Fumikatsu Nishizawa; Richard A. Staff; Keitaro Yamada; Ikuko Kitaba; et al. (Journal of Volcanology and Geothermal Research, 2025)

A detailed record of large explosive eruptions from Japan between ∼120 and 50 ka preserved at Lake Suigetsu - Sophie O. Vineberg; Paul G. Albert; Danielle McLean; Takehiko Suzuki; Richard A. Staff; Keitaro Yamada; Ikuko Kitaba; Junko Kitagawa; Christina J. Manning; Hannah M. Buckland; Gwydion Jones; Fumikatsu Nishizawa; et al. (Quaternary Science Reviews, 2024)

A luminescence-derived cryptostratigraphy from the Lake Suigetsu sedimentary profile, Japan: 45,000–30,200 IntCal20 yr BP - Richard A. Staff; David C.W. Sanderson; Charlie L. Rex; Alan Cresswell; Masayuki Hyodo; Ikuko Kitaba; Michael H. Marshall; Gordon Schlolaut; Keitaro Yamada; Yoshiaki Suzuki; Vanessa Nowinski; Ryuji Tada; et al. (Quaternary Geochronology, 2024)

Cryptotephra preserved in Lake Suigetsu (SG14 core) reveals the eruption timing and distribution of ash fall from Japanese volcanoes during the Late-glacial to early Holocene - Paul G. Albert; Danielle McLean; Hannah M. Buckland; Takehiko Suzuki; Gwydion Jones; Richard A. Staff; Sophie Vineberg; Ikuko Kitaba; Keitaro Yamada; Hiroshi Moriwaki; Daisuke Ishimura; Ken Ikehara; et al. (Quaternary Science Reviews, 2024)

Reliable radiocarbon dating of fossil pollen grains: It is truly possible - Takayuki Omori; Keitaro Yamada; Ikuko Kitaba; Tatsuo Hori; Takeshi Nakagawa (Quaternary Geochronology, 2023)

Understanding the human impact on Akita-sugi cedar (Cryptomeria japonica) forest in the late Holocene through pollen analysis of annually laminated sediments from Ichi-no-Megata, Akita, Japan - Junko Kitagawa; Yoshimune Morita; Miroslaw Makohonienko; Katsuya Gotanda; Kazuyoshi Yamada; Hitoshi Yonenobu; Ikuko Kitaba; Yoshinori Yasuda (Vegetation History and Archaeobotany, 2016)

Brief sea‐level fall event and centennial to millennial sea‐level variations during Marine Isotope Stage 19 in Osaka Bay, Japan - Kenta Maegakiuchi; Masayuki Hyodo; Ikuko Kitaba; Kotaro Hirose; Shigehiro Katoh; Hiroshi Sato (Journal of Quaternary Science, 2016)
Detailed sea‐level variation was investigated for Marine Isotope Stage (MIS) 19, based on diatom and grain size analyses of a marine sequence in a core of the Osaka Group. Diatom sea‐level proxies represent precession‐related signals correlated with highstands MIS 19.3 and 19.1, and lowstand MIS 19.2. Astronomical tuning shows the marine sequence has a uniform accumulation rate of about 60 cm ka −1 . A rapid sea‐level fall event was found in the earliest MIS 19, demonstrated by several independent sea‐level proxies of diatom and grain size. This event began with a rapid sea‐level drop, followed by a gradual recovery, at about 783–782 ka. A maximum abundance of pelagic diatom taxa at a core depth of 402.20 m evidently shows the highest sea‐level peak in MIS 19, supported by many other proxies. Based on the diatom data, sea‐level change across MIS 19.1 is characterized by centennial to millennial fluctuations. The sea‐level fall event began just after the onset of a cooling event previously reported from the same core. Observations of a comparable sea‐level fall signal in many deep‐sea core records suggest the event is global.